Changes in Peripheral Blood Neutrophils, Lymphocytes and IL-10 in Children with Kawasaki Disease from Different Age Groups Undergoing Intravenous Immunoglobulin: A Retrospective Study - Chun Zhang; Xuan Zhang; Jia Shen; Xiaotong Lu; Jian Zhang; Sun Chen (Mediators of Inflammation)
Immunoglobulin intravenous (IVIG) is widely used in mucocutaneous lymph node syndrome, known as Kawasaki disease (KD). However, the patients’ inflammatory response during usage remains unclear. In the present study, the association between inflammatory response and lymphocyte count in children with KD from different ages was evaluated before and after IVIG. The medical records of 50 children with KD were retrospectively reviewed and divided into five groups according to age. As compared with the data from healthy children, the relative neutrophil count of all children with KD was increased, and that of lymphocytes was decreased. The neutrophil/lymphocyte ratio (NLR) was different among all groups and was higher in children aged ≥4 years, as compared with other groups. Following IVIG, the relative neutrophil and lymphocyte counts of all children with KD returned to normal levels. The altered levels of neutrophils and lymphocytes were found to be linearly correlated. The correlation coefficient in the five groups was 0.99, 0.87, 0.91, 0.97 and 0.99, from young to old, respectively (p<0.01). The age of children with KD was positively correlated with older age (r=0.91, p=0.03). In patients aged ≥4 years, the absolute CD19+ B cell count prior to IVIG increased, and that increase was linearly correlated with the decrease in interleukin-10 (IL-10) following IVIG (r=0.71, p<0.05). The older the child’s age, the better the regulatory effect of IVIG on the KD child’s immune response and the recovery of immune equilibrium it achieved. In KD patients aged ≥4 years, the abnormally proliferating CD19+ B cells may be involved in the secretion of IL-10 to balance the humoral immunity. In such patients, the combination of the absolute CD19+ B cell count prior to IVIG and the decreased levels of IL-10 following IVIG may play a crucial role in evaluating the effect of IVIG in the inflammation.